Novo-Melnikovo: The impact of federal programs on the spatial development - Tumureeva, Maria; Gladkova, Ekaterina; Kozlov , Valery (project baikal, 2021)
The article considers the place of public spaces in the fabric of panel microdistricts, Pervomaisky and Universitetsky in Irkutsk. It analyses the current condition and problems of public spaces. It gives the examples of improvement of areas under the federal and regional programs on improving the comfort of urban environment. The specific features of the formation of a pedestrian boulevard in the given microdistricts are revealed and the necessary factors for the creation of a successful and frequented public place are identified.
Keywords: large scale development; comfortable urban environment; federal programs; public spaces; courtyard areas